Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3109/09553002.2014.925603
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced apoptosis varies among individuals and is modified by sex and age

Abstract: Purpose Although there are considerable data on mechanisms of radiation-induced apoptosis in vitro and in animal models, little is known about functional variation in these pathways in humans. We sought to develop a tractable system to evaluate this. Materials and methods Peripheral blood mononuclear cells were isolated from 90 healthy volunteers, divided into two aliquots, one irradiated with a 5 Gy dose and the other sham-treated (0 Gy), and assessed for damage-induced apoptosis after 24 hours. To investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Early studies reported that the survival rate of lymphocytes from elderly individuals after ex vivo irradiation is approximately one-half from that of lymphocytes from young individuals [ 68 ]. Discordantly, a more recent study found an age-associated decrease in IR-induced apoptosis [ 69 ], and this finding was also confirmed in later studies [ 70 , 71 ]. Regarding radiation-induced DNA strand breaks, the number of γ -H2AX foci is higher in young than in old mice, which partially correlated with cellular proliferation and expression of DNA repair proteins [ 72 ].…”
Section: Discussionsupporting
confidence: 79%
“…Early studies reported that the survival rate of lymphocytes from elderly individuals after ex vivo irradiation is approximately one-half from that of lymphocytes from young individuals [ 68 ]. Discordantly, a more recent study found an age-associated decrease in IR-induced apoptosis [ 69 ], and this finding was also confirmed in later studies [ 70 , 71 ]. Regarding radiation-induced DNA strand breaks, the number of γ -H2AX foci is higher in young than in old mice, which partially correlated with cellular proliferation and expression of DNA repair proteins [ 72 ].…”
Section: Discussionsupporting
confidence: 79%
“…We also identified that B cells of the peripheral blood were less resistant to radiation in comparison to T cells. Future analyses should take into account that cell death responses following radiation exposure might, under distinct microenvironmental conditions, be dependent on age and sex [ 55 ] as well as on the basal inflammatory state [ 7 , 8 ]. Our ex vivo/in vitro studies should also be considered as the first helpful basis to optimize (individualize) radiotherapy in multimodal settings, including for the definition of suited time points for further inclusion of immunotherapies or for reducing the cumulative dose of radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although this was primarily driven by our risk assessment, we recognize that future studies should be designed to include both sexes. Interestingly, since this study has been completed a study pointing out differences in the rate of apoptosis generated by exposure to irradiation has been published . In this study MNCs derived from females had a lower apoptosis rate (30.7%) than those derived from males (41%).…”
Section: Discussionmentioning
confidence: 99%